UMA GEOMETRIA DO ENSINO NA ESCOLA PRIMÁRIA MATO-GROSSENSE (1890-1930) - Klinton Pinheiros Sales (2023)
In this study, we examine the production related to guidelines for geometry teaching in official documents from the State of Mato Grosso during the period between 1890-1930. To achieve this aim, we are guided by the following inquiry: What geometry was recommended for public schools in Mato Grosso during the period of intuitive pedagogy? This study analyzes a time when proposals regarding the intuitive method were disseminated. Our analyses were directed with theoretical-methodological aspects derived from Cultural History authors: Julia (2001); Chervel (1990); and from the socio-historical perspective of Hofstetter and Schneuwly (2017), which focuses on professional knowledge (knowledge to teach and for teaching) and Morais, Bertini, and Valente (2017) who provide insights regarding the mathematics to teach and for teaching, as well as Valente (2020b) who discusses the mathematics of teaching. The primary goal of this research is to characterize the geometry education in public schools of Mato Grosso during the era of intuitive pedagogy; with specific objectives to analyze which knowledge to teach and for teaching geometry was present in the official documents directed at primary schools in Mato Grosso during the First Republic era; and to identify any potential transformations in the geometry education in Mato Grosso during the period under study. Data analysis revealed that the didactic-pedagogical organization was gradually transformed by regulations issued during the First Republic, introducing a new proposal typical of the intuitive era, indicating the necessity for additional knowledge for teachers to impart Euclidean geometry (subject of instruction). Thus, observation, visualization, and perception gained prominence in schools during the intuitive pedagogy era. Geometry instruction became more aligned with everyday life, shaped by situations experienced both inside and outside of school, transitioning from the concrete to the abstract in an analytic/synthetic progression. The intuitive pedagogy brought shifts in the school's purpose, witnessing changes in the roles of schools, teachers, and students, aiming to achieve knowledge that is practical and related to daily life. For example, teachers encountered a new knowledge, wherein they were expected to motivate students towards learning geometric content, manifesting in an intuitive, practical, and utilitarian geometry grounded in daily tasks. The teacher who taught geometric knowledge was placed under his responsibility with new professional knowledge, in the sense that his work must include knowledge in the order to be followed in teaching. In which the teacher must have knowledge of Euclidean geometry and its properties, and on the other hand, validate the properties through concreteness and observation, with the construction of drawings on the blackboard. In this way, the simple is in the concrete, linked to the child's everyday objects. Keywords: Mato Grosso; Official documents; Geometry of teaching.